Vulcan petawatt-operation and development - Hernandez-Gomez, C; Brummitt, P; Canny, D; Clarke, R; Collier, J; Danson, C; Dunne, A; Fell, B; Frackiewicz, A; Hancock, S; Hawkes, S; Heathcote, R; et al. (2006)
Petawatt capability on the Vulcan laser facility has been available to the international plasma physics community for over two years. This has enabled novel experiments to be carried out and new regimes of physics to be explored. During that time, there have been 10 successful user experiments with 89% of shots delivered within the requested energy limits. In the autumn of 2004, pulses with powers of more than a petawatt (10 15Watts) were delivered to target with energies greater than 400 J and pulse widths shorter than 500 femtoseconds (10 -15) on target. In parallel to the development of ultra-high intensity pulses is a programme to enhance Vulcan's long pulse capabilities. This paper will present an overview of the current capabilities of the Vulcan Petawatt facility and discuss some of the recent technological advances that have enabled the generation of Petawatt pulses. © EDP Sciences.